Pedagogical Bases of School Libraries in Ukraine Work (the Second Half of the XIX Century – 1920-s): Historiobiographic and Source Bsae of the Research - Pokusova, Olena (Pedagogical Discourse, 2013)
The article analyzes the historiography and source base of the research of pedagogical principles of work of school libraries in Ukraine (the second half of the twentieth century – 1920-s). It traces the conditions of development of historiography of the problem. The works of Soviet, Russian and Ukrainian historians and historians of pedagogy are analyzed, their pedagogical and historical views on the development of student libraries of the mentioned period are cleared up. The selected sources of research are characterized and perspectives in the study of the proposed problem are defined.